Safety through engaged workers: The link between Safety-II and work engagement. (February 2022) - Homann, Franziska; Limbert, Caroline; Bell, Nicholas; Sykes, Peter
Highlights: A synthesised review showed that Safety-II and work engagement rely on similar antecedents. A combined framework and principles were provided. Safety practitioners should consider their own role and influence in their workers' engagement levels and Safety-II mindset. Abstract: Safety-II (and related concepts such as 'Safety differently' ) are relatively recent developments in the field of health and safety management. The central argument of these approaches is that interventions should focus on collaborating with workers to understand and provide the resources that workers need to allow work to proceed successfully and safely. Safety-II relies upon workers volunteering information, meaningfully participating in discussions around the organisation of work, and being trusted. However, Ajslev et al. (2020) highlight the psychosocial barriers to 'participatory approaches'. Few papers have explored the psychosocial conditions in which modern, collaborative approaches to safety might flourish. To address this, this paper explores the similarities between the concepts of work engagement and Safety-II. In particular, this paper identifies that both rely on similar antecedents (such as certain leadership practices, promoting autonomy and creating a just organisation). The inference is that organisations that wish to implement modern, collaborative approaches to safety, will need to understand and address much wider issues regarding how workers are perceived and managed. This is the first paper to compare the antecedents of Safety-II and engagement, and also the first to present evidence that these two concepts complement each other.